Pengaruh Posisi Duduk Selama 3 Menit Setelah Induksi Spinal Anestesi terhadap Kejadian Hipotensi dan Bradikardi di RS PKU Muhammadiyah Gombong - Yunanto Adi Nugroho; Emiliani Elsi Jerau; Made Suandika; Magenda Bisma Yudha (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Hypotension and bradycardia are common complications following spinal anesthesia due to extensive sympathetic blockade, which can lead to hemodynamic instability and decreased perfusion of vital organs. A simple non-pharmacological preventive measure is maintaining a sitting position immediately after induction to limit the upward spread of hyperbaric anesthetic agents toward the thoracic region. This study aimed to determine the effect of maintaining a sitting position for three minutes after spinal anesthesia induction on the incidence of hypotension and bradycardia at PKU Muhammadiyah Gombong Hospital. The research employed a quasi-experimental design with a pre–post test with control group approach involving 69 respondents selected through consecutive sampling. The intervention group (n = 34) maintained a sitting position for three minutes, while the control group (n = 35) was immediately placed in a supine position. Blood pressure and heart rate were observed at 5, 10, and 15 minutes after induction, and the data were analyzed using Chi-Square and binary logistic regression tests. The results showed that the incidence of hypotension and bradycardia was significantly lower in the intervention group (p < 0.05), indicating that the sitting position acted as a protective factor. In conclusion, maintaining a sitting position for three minutes after spinal anesthesia induction effectively reduces the incidence of hypotension and bradycardia and is recommended as a simple strategy to enhance patient hemodynamic stability.